School and career guidance in a Portuguese public school (1969-1970) - Silva Freire, Mário (Aprender, 2024)
A description of a school and career guidance action carried out in a Portuguese public school, Liceu de Portalegre, during the 1969-1970 academic year, conducted by a guidance expert trained in the 1960s by the Instituto de Orientação Profissional. It involved all 251 students in the 5th, 6th, and 7th grades attending the school. Of those, 40 students were administered tests from the pool used at the time by the Instituto de Orientação Profissional. This Institute, founded in 1925, and the work developed by its founder, Faria de Vasconcelos, were references for research in the field of vocational guidance, selection, and work psychology internationally. They contributed to contextualizing this study. This action, revealing a markedly psychometric approach on the students subjected to tests, attempts to go beyond it with all students involved, both through information, based on a documentary collection that was organized, about the public and private courses that existed at the time and the respective professions to which they pointed, and through the involvement of the respective parents. There are no records of any other school and career guidance action, before 1970, in a Portuguese public school.
Keywords: Faria de Vasconcelos; Institute of Vocational Guidance; Liceu de Portalegre; school and career guidance; guidance expert